GROWTH DYNAMICS OF THE PHYSIOGNOMIC HEIGHT OF THE FACE IN CHILDREN AGED 7-12 YEARS (Scientific journal of the Fergana State University, 2023)
The article describes the results of a craniometric study conducted among boys and girls living in Izboskan district of Andijan region in order to analyze the growth dynamics of the physiognomic height of the face in children aged 7-12 years. In particular, this scientific article presents the goals and tasks of craniometry, the importance of craniometric research today, the results of the conducted research, its analysis, the indicators of the physiognomic height of the face in boys and girls of every age from 7 to 12 years.